\(sin^2a+cos^2a-sin^4a-2cos^2a+sin^2a\)
\(=2sin^2a-cos^2a-sin^4a\)
\(=2sin^2a-cos^2a-\left(\frac{1-cos2a}{2}\right)^2\)
khai triển ra rồi quy đồng lên
\(=\frac{8sin^2a-4cos^2a-1+2cos2a-cos^22a}{4}\)
Mà \(2cos2a=2\left(cos^2a-1\right)=4cos^2-2\)
\(\Rightarrow\frac{8sin^2a-cos^22a-3}{4}\)
Mà \(-cos^22a=sin^22a-1=4sin^2cos^2-1\)
\(\Rightarrow\frac{8sin^2a+4sin^2a.cos^2a-4}{4}\)
\(=\frac{4sin^2a.\left(2-cos^2a\right)-4}{4}\)
\(=sin^2a\left(1+sin^2a\right)-1\)
\(=sin^4a-cos^2a\)
viết lại đề đi cậu ơi